Toxicity and binding capacity of Cry1 proteins to Helicoverpa armigera (Lepidoptera: Noctuidae) intestine receptors - Sebastião, Isis; Lemes, Ana Rita Nunes; Figueiredo, Camila Soares; Polanczyk, Ricardo Antonio; Desidério, Janete Apparecida; Lemos, Manoel Victor Franco (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the toxicity and the binding capacity of the Cry1Aa, Cry1Ab, Cry1Ac, and Cry1Ca proteins, from Bacillus thuringiensis, to Helicoverpa armigera intestine receptors. Binding analysis of the activated proteins to the brush‑border membrane vesicles (BBMV) in the midgut of H. armigera, besides heterologous competition assays to evaluate their binding capacity, was performed. Cry1Ac stood out as the most toxic protein, followed by Cry1Ab and Cry1Aa. The Cry1Ca protein had no toxicity to the caterpillars and, therefore, it was not possible to evaluate its LC50 and LC90 toxicity parameters. The Cry1Aa, Cry1Ab, and Cry1Ac proteins are able to bind themselves to the same receptor in the midgut membrane, which increases the risk of developing cross‑resistance. Therefore, the use of these proteins together should be avoided.